The Israeli-Palestinian Conflict: Implications for the Principles of Distinction and Self-Defence in International Humanitarian Law - Nabiebu, Miebaka; Alobo , Eni Eja; Ijiomah, Amarachukwu Onyinyechi; Ipuole, Roland Okayi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Armed conflicts, stemming from socio-economic, political, religious, and security factors, have persisted throughout human history. The Israeli-Palestine conflict stands as a prolonged example, while post-Cold War conflicts by non-state actors have also emerged. International Humanitarian Law (IHL) introduced principles of self-defence and distinction to safeguard civilian populations during such conflicts, yet both state and non-state actors often disregard them. Israel, in its conflict with Palestine, adopted targeted killing (TK) to uphold these principles, as Nigeria did during its 1967–1970 civil war. However, permanent members of the UN Security Council often prioritise their own rules of engagement, neglecting self-defence and distinction. This undermines justice, epitomising the “might is right” ideology, as evidenced by Russia’s destruction of civilian infrastructure in Ukraine. Urgent reform of the Security Council is imperative, considering these alarming trends. This article scrutinises ongoing armed conflicts, including the Israeli-Palestine conflict, the Nigerian civil war, and conflicts involving powerful nations like the USA, Iraq, Afghanistan, Ukraine, and Russia. It employs doctrinal, analytical, comparative, and descriptive methodologies to assess the observance of self-defence and distinction principles. Findings reveal Palestine’s instigation of the Israeli-Palestine conflict, powerful nations’ preference for their Rules of Engagement, and the over-politicisation of the Security Council through veto power. Proposed reforms include the domestication of Geneva Conventions and Protocols, expanding the Security Council’s permanent membership to include African, Latin American, and South American countries, and developing rules for terrorist groups.